Edukasi Game Pengenalan Makanan Tradisional Indonesia Menggunakan Unityi2d - Maisyaroh, Maisyaroh; , Fatah Yasin Al Irsyadi, S.T., M.T (2016)
The traditional food is a food commonly eaten since several generations, with food used as the identity of a country that can differentiate with other countries, as well as the state of Indonesia which has a variety of typical foods in each region. Technology is one of the means or tools to introduce traditional foods, such as online and offline games which introduce and teach about food, recipes and the way how to make it. However, the games which are available on internet commonly introduce outside or foreign food and fast food dishes such as sara cooking games, and Cooking Games. Thus, the lack of Traditional food games influence people to play games with Non-local menu than Local menu. Caused by the problem above, the researcher aims to design and create a game which introduce Indonesian traditional food, thus, while playing game people also learn about their own traditional food, that can be operated using a computer and gadget. The making process of this educational game use several methods, namely, Methods characters, character display that supports two chefs. The object that is used is the introduction of food and Recipes to give any information about material used in the menu. Application development it begins with a storyboard game, then supporting software to create educational game. This Educational Game shows a game of cooking stages or process and has quizzes taken while running the game. The result of this research is an application of educational game introducing of Indonesian traditional food using Unity2d applications as game building, playmaker as programming, Corel Draw to create objects and, as a processor, an audio format factory. The conclusion of this educationl game is an application that can be operated using a PC, laptop and gadgets using Android apps.